2016
DOI: 10.3389/fnut.2016.00052
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Consumption and General Health in Secondary School Children: A Cross-sectional and Longitudinal Analysis

Abstract: Although caffeine is sometimes associated with beneficial effects in adults, the substance may be dangerous if intake is too high. This concern is particularly relevant in regards to children and adolescents, as consumption of energy drinks may be particularly high in such populations. For this reason, the current study examined data from the Cornish Academies Project to determine whether caffeine intake in secondary school children was related to responses to a single-item measure of general health. Two cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This article presents secondary analyses of the Cornish Academies Project [19,[28][29][30][31], a longitudinal study with time points six months apart, investigating the relationship between healthrelated behaviours and well-being and educational outcomes for secondary students with SEN [38]. The students were classified as having SEN based on information from the School Information Management System (SIMS), but there was no further information on the type of SEN. Information from the teachers suggested that the types of SEN represented in the sample were mainly autism, ADHD and mental health problems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article presents secondary analyses of the Cornish Academies Project [19,[28][29][30][31], a longitudinal study with time points six months apart, investigating the relationship between healthrelated behaviours and well-being and educational outcomes for secondary students with SEN [38]. The students were classified as having SEN based on information from the School Information Management System (SIMS), but there was no further information on the type of SEN. Information from the teachers suggested that the types of SEN represented in the sample were mainly autism, ADHD and mental health problems.…”
Section: Methodsmentioning
confidence: 99%
“…These mental health questions were taken from the Well-being Process Questionnaire [11]. Finally, participants were asked two questions, the first to indicate how many hours per night they typically slept and the second to indicate how well they rated their overall health over the past six months (1 = very good, 2 = good, 3 = fair, 4 = poor, 5 = very poor) [38].…”
Section: Methodsmentioning
confidence: 99%
“…Caffeine intake is also associated with both health-related behaviours (e.g. sleep, Richards and Smith, 2016b) and health (Richards & Smith, 2016, b, c, d)…”
Section: Possible Confounders: Health and Health-related Behavioursmentioning
confidence: 99%
“…5 It is found in common beverages and products such as coffee, tea, and soft drinks, along with cocoa and chocolate, and various pharmaceutical and dietary supplements. 6 In Indonesia, there are many types of Arabica coffee, especially in East Java. Arabica coffee has a higher caffeine content than Liberica type, but lower than Robusta type coffee.…”
Section: Introductionmentioning
confidence: 99%